MiR-3188 Inhibits Non-small Cell Lung Cancer Cell Proliferation Through FOXO1-Mediated mTOR-p-PI3K/AKT-c-JUN Signaling Pathway - Wang, Chunyan; Liu, Enqi; Li, Wen; Cui, Jue; Li, Tongxiang (Frontiers in Pharmacology, 2018)
This study investigated the role of miR-3188 on the proliferation of non-small cell lung cancer cells and its relationship to FOXO1-modulated feedback loop. Two non-small cell lung cancer (NSCLC) cell lines A549 and H1299 were used. RNA silencing was achieved by lentiviral transfection. Cell proliferation was assessed by immunohistochemical staining of Ki67 and PCNA, Edu incorporation, and colony formation assay. Western blotting was used to examine expression of FOXO1, mTOR, p-mTOR, CCND1, p21, c-JUN, AKT, pAKT, PI3K, p-PI3K, and p27 proteins. It was found that miR-3188 reduced cell proliferation in NSCLC cells. Molecular analyses indicated that the effect of mammalian target of rapamycin (mTOR) was directly mediated by miR-3188, leading to p-PI3K/p-AKT/c-JUN inactivation. The inhibition of this signaling pathway further caused cell-cycle suppression. Moreover, FOXO1 was found to be involved in regulating the interaction of miR-3188 and mTOR through p-PI3K/p-AKT/c-JUN signaling pathway. Taken together, our study demonstrated that miR-3188 interacts with mTOR and FOXO1 to inhibit NSCLC cell proliferation through a mTOR-p-PI3K/AKT-c-JUN signaling pathway. Therefore, miR-3188 might be a potential target for the treatment of NSCLC.